Morphological, anatomical and genetic diversity of Nanhaia speciosa (Champ. ex Benth.) J.Compton & Schrire from Northern Vietnam - PHONG XUAN ONG; CUONG BA CAO; DO TAN KHANG; TRAN GIA HUY; PHI BANG CAO; HA DUC CHU; DINH VAN NGUYEN; HONG VIET LA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Ong PX, Cao CB, Khang DT, Huy TG, Cao PB, Chu HD, Nguyen DV, La HV. 2024. Morphological, anatomical and genetic diversity of Nanhaia speciosa (Champ. ex Benth.) J.Compton & Schrire from Northern Vietnam. Biodiversitas 25: 1174-1184. Nanhaia speciosa (Champ. ex Benth.) J.Compton & Schrire has been considered a captivating plant species known for its remarkable attributes and contributions to ecological systems and human use. This medicinal plant originated from tropical Southeast Asia regions. However, the investigation of this species in Vietnam has been still lacking. This study comprehensively analyzed N. speciosa samples obtained in Vietnam; the morphological and anatomical characteristics of N. speciosa leaflets and flower samples collected from different regions were analyzed. As a result, the structural components of the flower were slightly similar between these samples, whereas the leaflet shape exhibited variations in the leaflet base, petiole, and leaflet apex. According to the ISSR and RAPD analysis, we demonstrated that N. speciosa found in ND genotypes (Tan Yen, Bac Giang) exhibited clearly different genetic backgrounds from CSS (Loc Binh, Lang Son) and CSD (Son Dong, Bac Giang) genotypes. Based on the clustering diagram of ISSR markers, 15 plant genotypes were classified into 2 large clusters, A and B, with genetic similarity ranging from 0.62 to 0.90. The RAPD dendrogram illustrated two main clusters, C and D, with genetic similarity ranging from 0.57 to 0.92. Therefore, this study could provide a solid foundation for identifying and characterizing N. speciosa species in Vietnam and a direction for advanced research on conservation, sustainable breeding, and exploiting pharmaceutical values.